Geographic Distribution of Hantaviruses Associated with Neotomine and Sigmodontine Rodents, Mexico - Mary L. Milazzo; Maria N.B. Cajimat; Hannah E. Romo; Jose G. Estrada-Franco; L. Ignacio Iñiguez-Dávalos; Robert D. Bradley; Charles F. Fulhorst (Emerging Infectious Diseases, 2012)
To increase our knowledge of the geographic distribution of hantaviruses associated with neotomine or sigmodontine rodents in Mexico, we tested 876 cricetid rodents captured in 18 Mexican states (representing at least 44 species in the subfamily Neotominae and 10 species in the subfamily Sigmodontinae) for anti-hantavirus IgG. We found antibodies against hantavirus in 35 (4.0%) rodents. Nucleotide sequence data from 5 antibody-positive rodents indicated that Sin Nombre virus (the major cause of hantavirus pulmonary syndrome [HPS] in the United States) is enzootic in the Mexican states of Nuevo León, San Luis Potosí, Tamaulipas, and Veracruz. However, HPS has not been reported from these states, which suggests that in northeastern Mexico, HPS has been confused with other rapidly progressive, life-threatening respiratory diseases. Analyses of nucleotide sequence data from 19 other antibody-positive rodents indicated that El Moro Canyon virus and Limestone Canyon virus are geographically widely distributed in Mexico.